A Hybrid Condition-Based Maintenance Model for Deteriorating Systems Subject to Nonmemoryless Imperfect Repairs and Perfect Replacements - Huynh, Khac Tuan (IEEE transactions on reliability, 2020)
Condition-based maintenance (CBM) is popularly recognized as a key lever that enables organizations to gain a competitive advance in the context of the fourth industrial revolution. Combining both the perfect and imperfect maintenance actions into CBM policies seems to be an efficient way to achieve high economic performances. Following this view, we propose and optimize in this article a hybrid deterioration-based maintenance model for continuously deteriorating systems subject to nonmemoryless imperfect repairs and perfect replacements. Compared to existing related works, the originality of our model is threefold. First, an innovative model representing both the positive and memory effects of imperfect repairs is developed. Second, a new decision rule for switching between perfect and imperfect maintenance actions is proposed. Finally, the mathematical cost model of the proposed hybrid maintenance policy is fully formulated on the basis of the sophisticated semiregenerative theory. Numerous sensitivity studies and comparisons with benchmark policies under various configurations of maintenance costs and system characteristics allow to better understand the behaviors of our hybrid maintenance policy and to confirm its effectiveness.